Starting from scratch: realities of older Maltese ex-sisters - Marisa, Cannataci; Maria Aurora, Fenech (Magyar Gerontológia, 2023)
Statistics have revealed how not only globally but also in Malta the number of women religious has decreased. This study delved into the experiences of older ex-sisters from apostolic congregations who held simple vows, lived in the convent, subsequently leaving the congregation.